First Captive Born Sunda Pangolin (Manis javanica Demarest, 1822) in Malaysia - Cosmas, Ngau; Hafizul, Fahmi; Mohamad, Faizal; Yusoff, Shariff; Zubaidah, Kamarudin; Rahmat, Topani; Abdul Kadir, Abu Hashim; Jeffrine Rovie, Ryan Japning (Department of Wildlife and National Parks, 2021)
Sunda pangolin (Manis javanica Desmarest, 1822), also known as Malayan or Javan pangolin, is one of four species of pangolin available in Asia that includes Indian pangolin (Manis crassicaudata E. Geoffroy, 1803), Chinese pangolin (Manis pentadactyla Linnaeus, 1758), and Philippine pangolin (Manis culionensis de Elera, 1915). The remaining four species are from the African lineage, which are the white-bellied pangolin (Phataginus tricuspis Rafinesque, 1821), African black-bellied pangolin (Phataginus tetradactyla Linnaeus, 1766), Giant pangolin (Smutsia gigantean Illiger, 1815), and Temminck's pangolin (Smutsia temminckii Smuts, 1832). Figure 1 shows the species ranges of the pangolin species on the African and Asian continents.